KEHUJJAHAN HADĪṠ I’MAL LIDUNYĀ KAANNAKA TA’ISḤU ABADAN WA’MAL LIAKHIROTIKA KAANNAKA TAMŪTU : Godan Sebagai Dalil Etos Kerja - Nasrun, Mahdalena (Al-Iqtishadiah: Jurnal Hukum Ekonomi Syariah, 2022)
I’mal liddunyā kaannaka ta’īsyu abadan, wa’mal liākhirotika kaannaka tamūtu godan very famous often quoted in various scientific articles. Whereas in fact, after reviewed furthermore this hadīṡ contradicts with the texts of the al-quran. The question in this research is whether this is a hadīṡ? how is the hujjah hadīṡ i'mal liddunyaa kaannaka?. This research including a research library with approach a critical theory of matan hadīṡ. The results of the research show that this is not a hadīṡ, it is not found in the hadīṡ mu'tabar book; kutub al-tis'ah.Therefore this is just an expression (aṡar), in terms of sanad it is not marfu', not hadīṡ la ashla lahu. The source of this aṡar is thought to be from Ibn 'Umar, from Ali bin Abi Talib ra, from the words of 'Umar bin al-As. Matan criticism theory is used to evaluate aṡar, including its in not applicable (gair ma'mul bih). Contrary to a higher dalil, namely the al-quran. QS aż-Żāriāt verse 56 explains the essence of the purpose of human creation, namely to worship Allah SWT. In rhythm with QS al-Jumuah (62): 10) the order after praying is to seek sustenance. Likewise the same command to be balanced between the affairs of the hereafter and the world in QS al-Qaṣaṣ (28): 77. These verses are rules, guidelines, the spirit of motivation in carrying out every activity of human life in the world.